Enhancing Literacy: The Reading Development of Grade School Learners - Balaquidan, Recy DG; Caballero, Alex; Quitolbo, Ruben Pandi (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2025)
The research studied how parent learning action cells (PLACs) can improve reading skills for non-readers and struggling readers using different teaching methods. It aimed to see how PLACs affect vocabulary, comprehension, and fluency. The mixed-methods approach of the study highlighted strategies parents can use, like phonics, sight words, and comprehension techniques. Results showed that students improved their reading skills after PLACs, and there was a strong link between parents' participation and post-assessment scores. Parents noted that their child felt more confident in reading, improved comprehension, better understanding of reading strengths and weaknesses, a desire to continue reading together, and the importance of spending time reading with their child.